Exploring halal groceries purchase intention of Muslim customers at artisanal grocery stores / Nur Shahrulliza Muhammad … [et al.] - Muhammad, Nur Shahrulliza; Mohd Fuad, Fareez Redza; Mohamed Thaheer, Ahmad Shazeer; Hamdan, Fairus (Faculty of Business and Management, Universiti Teknologi MARA, Shah Alam, Malaysia, 2019)
Gone were the days where groceries were marketed in boring, old-school grocery stores. In Malaysia, grocery store scene is embracing the emergence of artisanal foods, foreign and locally produced, with and without halal certification as part of the marketplace and has been driven by demand among consumers for authentic, gourmet and specialized groceries. Artisanal grocery stores play a critical role in providing visitors destinations with unique groceries and in growing the food tourism industry by elevating groceries to a whole new level in which line of products available at the stores appear to be distinctive and classy. This study aimed to explore purchase intention of halal groceries by Muslim customers at artisanal grocery stores. Tested variables were Halal Awareness, Halal Certification, Promotions of Halal Products, Attitude and Religious Beliefs. Findings were derived from 100 self-administered questionnaires at two leading artisanal grocers in Malaysia located in Klang Valley. Evidently, Attitude has the most influence on Muslim customers’ intention to purchase halal groceries at these stores.